Transverse Upper Gracilis Flap Breast Reconstruction: A 5-Year Consecutive Case Series of Patient-Reported Outcomes. Issue 2 (3rd June 2022) - Jessica, Anne Savage; Zhao, Jade; Mackey, Simon; Blackburn, Adam Victor
Abstract : Background: The transverse upper gracilis flap is an important reconstructive option for patients who desire autologous reconstruction after mastectomy but in whom a deep inferior epigastric perforator flap is unavailable or undesirable. The authors present an analysis of outcomes and patient satisfaction results, from a consecutive series in a single institution. Methods: Using a prospectively populated free flap database, all patients undergoing transverse upper gracilis flap breast reconstruction for a mastectomy defect between January of 2013 and December of 2017 were identified. Retrospective review of clinical notes, admissions, and discharge information was conducted to identify outcomes, secondary operations, and complications. All patients were contacted by letter and invited to take part in a patient satisfaction survey a minimum of 12 months after free-flap surgery. Results: Seventy-eight patients underwent transverse upper gracilis flap breast reconstruction using a total of 103 transverse upper gracilis flaps to reconstruct 99 breast mounds in the 5-year period studied. Patient satisfaction is evidenced by BREAST-Q scores showing 81 ± 19 percent Satisfaction with Breasts, 80 ± 20 percent Psychosocial Well-Being, and 84 ± 19 percent Physical Well-Being of the chest. Forty-six of 53 (87 percent) report satisfaction with the postoperative appearance of their thigh unclothed and 51 of 53 (96 percent) report satisfaction clothed. Conclusions: This is the first consecutive series of transverse upper gracilis flap breast reconstruction outcomes that presents BREAST-Q scores for multiple, postoperative reconstruction modules and details complications stratified by Clavien-Dindo score. The methodology can be easily replicated and benchmarked against. Our donor-site complication rates are lower than previous publications and patient satisfaction data reveal that this is a well-accepted option for patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.